Pinpointing change in virtual reality assisted treatment for violent offenders: a pilot study of Virtual Reality Aggression Prevention Training (VRAPT) - Ivarsson, David; Delfin, Carl; Enebrink, Pia; Wallinius, Märta (Frontiers in Psychiatry, 2023)
Preventing relapse into violence and its destructive consequences among persistent re-offenders is a primary concern in forensic settings. The Risk-Need-Responsivity framework models the best current practice for offender treatment, focused on building skills and changing pro-criminal cognitions. However, treatment effects are often modest, and the forensic context can obstruct the delivery of interventions. Developing treatments for offenders should focus on the best method of delivery to make “what works work.” Virtual reality (VR)-assisted treatments such as Virtual Reality Aggression Prevention Training (VRAPT) are a new and innovative approach to offender treatment. This pilot study followed 14 male violent offenders who participated in VRAPT in a Swedish prison context and measured changes from pre-treatment to post-treatment and 3-month follow-up in targeted aggression, emotion regulation, and anger. It also investigated potential impact factors (pro-criminal cognitions, externalizing behaviors, psychosocial background, and childhood adverse experiences). In Bayesian linear mixed effects models, participants showed a high probability of change from pre-treatment to post-treatment and to follow-up on all outcome measures. All outcome measures demonstrated a low probability of change from post-treatment to follow-up. Analysis of reliable change showed that participants’ results ranged from recovery to deterioration. We discuss the implications of the study for VRAPT’s impact on the target group, those who might benefit from the approach, and suggested foci for future studies in the field of VR-assisted offender treatment. The study was preregistered at the International Standard Randomized Controlled Trial Number registry (https://doi.org/10.1186/ISRCTN14916410).